PENGARUH PEMBERIAN FUNCTIONAL ELECTRICAL STIMULATION (FES) TERHADAP SKALA NYERI SUBLUKSASI SHOULDER PADA PASIEN POST STROKE DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Sabirin Berampu; Iramanda Sari Brampu; Isidorus Jehaman (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
Science and technology today become an inseparable part of the technology of modern society's life. Functional Electrical Stimulation (FES) to support recovery of upper limb after stroke. This research is a quantitative research with a quasi-experimental / quasi-experimental approach to the research design using pre-test and post-test. Determination of the number of samples using the Purposive Sampling method and get a sample of 12 people. Data collection was carried out by direct interview using observation sheets. The independent variable in this study is Functional Electrical Stimulation (FES) while the dependent variable is the Shoulder Subluxation Pain Scale. The assessment of shoulder subluxation pain scale includes a mild pain scale category of 6 people (50%), and moderate pain 4 people (33.3%) and very severe pain 2 people (16.7). Statistical test using Paired Sample T-test with Î± = 0.05. The results of the analysis show that there is a significant influence between the provision of Functional Electrical Stimulation (FES) on the scale of shoulder pain subluxation in post-stroke patients, ie with a p value (0.001â‰¤0.05). The conclusion of this study is that there is an influence between Functional Electrical Stimulation (FES) with Shoulder Subluxation Pain. Advice can be given is expected for post stroke patients and family support to pay attention to the patient's monotonous sleeping position.